Tensile Behavior of Parts Manufactured Using a Material Extrusion Process from a Filament with Short Carbon Fibers and PET Matrix - Blaj, Madalina; Zaharia, Sebastian-Marian; Morariu, Cristian Olimpiu; Pop, Mihai Alin; Cosnita, Mihaela; Oancea, Gheorghe (Processes, 2024)
One of the latest tendencies in research related to material extrusion based on additive manufacturing is to determine the mechanical characteristics of parts taking into consideration the most influential manufacturing parameters. The main research objective is to describe how the manufacturing parameters, part orientation, layer thickness and infill density influence the tensile behavior of specimens made from PET with 15% short carbon fibers. The most advantageous result is obtained for a layer thickness of 0.15 mm, with 100% material infill, and material deposition on the longitudinal direction of the part. The obtained mean values are: 65.4 MPa tensile strength, 1.93% strain at rupture, and 9 GPa Young Modulus. For these values, the tensile behavior of specimens manufactured along transverse and thickness directions are presented. The least favorable results are obtained for manufacturing by thickness. The novelty of the discussed research consists in all these aspects together with an original mathematical model that was determined based on design of experiments with a correlation of the regression model of over 90%. By optical and electronic microscopy material gaps are visible in the filament and manufactured parts, and the failure occurs in most cases in form of matrix cracks and delamination.
Keywords: MEX process; PET; short carbon fibers; mechanical properties; microscopy; manufacturing defects